Gestational diabetes: Screening for all, which test and which treatment? - Visser, Gerard H.A.; De Valk, Harold W. (Taylor and Francis Ltd., 2012)
Gestational diabetes mellitus is rapidly increasing in incidence, due to lifestyle changes, increasing obesity and maternal age. This increase makes universal screening mandatory; however, we are still far from it. Moreover, should we adopt rather strict oral glucose tolerance test cutoff values, resulting in a worldwide incidence of gestational diabetes mellitus of approximately 17.5%, or should we be more liberal and focus more on patients and offspring at increased risk, for example, obese women. Finally, are oral antidiabetic drugs such as glyburide and metformin safe enough to use in gestational diabetes mellitus, or should they still be considered as the 'poor man's insulin'? These issues were presented and discussed during lively debates at the Controversies in Obstetrics, Gynecology and Infertility annual meetings, but consensus was not reached.
Keywords: gestational diabetes; oral antidiabetic drugs; screening; Endocrinology, Diabetes and Metabolism